2021
DOI: 10.5688/ajpe8041
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Study Assessing the Effect of Cognitive Test Anxiety on Academic and Standardized Test Performance

Abstract: Objective. To evaluate the degree of cognitive test anxiety (CTA) present in student pharmacists at multiple pharmacy programs in the United States and to determine if there are associations between self-reported CTA and relevant academic outcomes. Methods. All 2018-2019 advanced pharmacy practice experience (APPE) students from three US Doctor of Pharmacy (PharmD) programs (N5260) were invited to participate in the study. Participants completed a validated 37-question survey that included the Cognitive Test A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…These items may contribute to test anxiety as learners wrestle to retrieve drug characteristic knowledge within the given timeframe based on the requested information or scenario presented. This additive effect may worsen the negative influence of test anxiety documented in the literature on academic performance, problem-solving abilities, reduced self-efficacy, and decreased perception of self-worth [ 12 , 22 ]. It is also worth noting that the definitive thresholds for competency are unclear in pharmacy and medical education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These items may contribute to test anxiety as learners wrestle to retrieve drug characteristic knowledge within the given timeframe based on the requested information or scenario presented. This additive effect may worsen the negative influence of test anxiety documented in the literature on academic performance, problem-solving abilities, reduced self-efficacy, and decreased perception of self-worth [ 12 , 22 ]. It is also worth noting that the definitive thresholds for competency are unclear in pharmacy and medical education.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns are equally notable in this study. Circumstantial factors such as student stress levels, timing of summative assessment (e.g., right before finals week), and personal mental health considerations may also influence student performance [ 12 ]. Faculty members and teaching assistants involved in the implementation of this study spent considerable time writing, vetting, overseeing, and assessing the pilot (>350 h, 840 questions).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Чини се да механизми суочавања са евалуативним стресом (нарочито стратегије превладавања усмерене на емоције) представљају значајне медијатор варијабле у релацији између висине изражености испитне стрепње и когнитивне перформансе (Ader & Erktin, 2010;Genc, 2017). Надаље, показало се да испитно анксиозни студенти изразито често упражњавају понашања из категорије избегавања, са посебним акцентом на прокрастинацији (Burcaş & Creţu, 2020;Pate et al, 2021;Wuthrich, Jagiello & Azzi, 2020).…”
Section: уводunclassified
“…It would appear that mechanisms for coping with evaluative stress (particularly emotion-focused strategies) constitute significant mediator variables in the relation between test anxiety levels and cognitive performance (Ader & Erktin, 2010;Genc, 2017). Furthermore, it has been shown that students with test anxiety are particularly prone to avoidance behaviors, especially procrastination (Burcaş & Creţu, 2020;Pate et al, 2021;Wuthrich, Jagiello & Azzi, 2020).…”
Section: Introductionmentioning
confidence: 99%